LOVE AND FEUD AS SEEN THROUGH THE CHARACTER HEATHCLIFF IN “WUTHERING HEIGHTS” BY EMILY BRONTE = TÌNH YÊU VÀ THÙ HẬN THỂ HIỆN QUA NHÂN VẬT HEATHCLIFF TRONG TÁC PHẨM “ĐỒI GIÓ HÚ” CỦA EMILY BRONTE - Trần, Thị Hạnh (2020)
The author, with her personal interest in Literature in general and Emily Bronte’s literary works in particular speaking, carried out this study to investigate the nature of love and feud in the novel “Wuthering Heights”. Within the limitation of time and length allowance, the author could only focused on analyzing the love and feud of Heathcliff – one of the main characters in the novel. Throughout the study process, reading and evidence-based analyzing were the most important methods used, though referencing was indispensable. The study resulted in some findings about the nature of Heathcliff’s love for Catherine such as its state of being unconditional, passionate, sacrificial, pure, tragic, immoral, obsessive, and mortal. Besides, the causes of his feud – including both explicit and implicit ones - were also found, the result of the research also pointed out that the deepest reason for Heathcliff’s love was the social class discrimination. Within the research duration, the author was specially attracted by the Gothic aspects in the novel, however, she did not manage to include it in her study. As a result, this should be an interesting topic to investigate in further studies relating to “Wuthering Heights”.